(3GdQbGHI Ydi GdJcjja GdbGfhfi ai GdehGO GdLfGFjI (B: s (3OQGSI ebGQfI ai GdJTQjYGJ GdeUQi h GdaQfSi h GdGdeGfi h GdHMQjfi (B/ s - (3CMeO YHOGdMcje YKeGf YHOGddgs; (3CMeO YhV HdGd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb , LGeYI GdbGgQI(B: s, 2017)
(3dbO JhUd GdacQ GdbGfhfi Gdi eG jSei HGdJcjja(B: (3h gh geRg GdhUd eGHjf GdhbGFY GdeYQhVg Ydi GdbGVi h GdbGfhf GdefWHb YdjgG h HOhf GdJcjja jJNHW GdbGVi ai GdMd GdbGfhfi ddfRGY GdeYQhV Ydjg h ef Ke JJSe Mdhdg HGdZehV h JNdh ef Gdaf h GdefWb h ef NdGd OQGSI GdJcjja GdbGfhfi JHjf Gf GdJcjja GdbVGFi h Gf cGf ef WHjYI GLQGFjg GdG Gf OhQ GdbGVi GdLfGFi ebjO HGdbGfhf GdehVhYi (B((3bGfhf GdYbhHGJ h GdJTQjYGJ GdLfGFjI GdNGUI(B) (3h GdHGMK dG jDjO GdJaQbI Hjf GfhGY GdJcjja GdbGfhfi h NGUI GdJcjja GdbVGFi HGYJHGQ Gf GdJcjja GdJTQjYi gh GdfehPL GdbGfhfi ddLQjeI Gh GdhGbYI GdLfGFjI ceG GhQOgG GdeTQY(B: (3h ef Ke aEf hUa GdeTQY Gh Jcjjag gh GdfehPL GdbGfhfi ddLQjeI CeG GdJcjja GdbGfhfi GdPi jeGQSg GdbVGA agh ddGYdGf Gh GdcTa Yf GdbGYOI GdbGfhfjI ai VhA GQGOI GdeTQYs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2017s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJcjja GdbGfhfi s; (3GdQbGHI Ydi GdJcjja GdbGfhfis; (3GdehGO GdLfGFjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs